Art Cinema and Theology: The Word Was Made Film - Ponder, Justin (Springer International Publishing, 2017)
This book examines postmodern theology and how it relates to the cinematic style of Robert Bresson, Carl Theodor Dreyer, Ingmar Bergman, and Luis Buñuel. Ponder demonstrates how these filmmakers forefront religious issues in their use of mise en scène. He investigates both the technical qualities of film “flesh” and its theological features. The chapters show how art cinema uses sound, editing, lighting, and close-ups in ways that critique doctrine’s authoritarianism, as well as philosophy’s individualism, to suggest postmodern theologies that emphasize community. Through this book we learn how the cinematic style of modernist auteurs relates to postmodern theology and how the industry of art cinema constructs certain kinds of film-watching subjectivity.
https://katalog.adlr.link/Record/51-9783319585550